1)Zn⁰ + H₂⁺¹S⁺⁶O₄⁻²(к) = Zn⁺²S⁺⁶O₄⁻²+ H₂⁺¹S⁻²↑ + H₂⁺¹O⁻²
Zn⁰ - 2ē -> Zn⁺² │2│1│4
S⁺⁶ + 8ē -> S⁻² │8│4│1
4Zn + 5H₂SO₄(к) = 4ZnSO₄ + H₂S↑ + 4H₂O
2) Cu⁰ + H₂⁺¹S⁺⁶O₄⁻²(к) = Cu⁺²S⁺⁶O₄⁻² + S⁺⁴O₂⁻² + H₂⁺¹O ⁻²
Cu⁰ - 2ē -> Cu⁺² │2│1
S⁺⁶ + 2ē -> S⁺⁴ │2│1
Cu + 2H₂SO₄(к) = CuSO₄ + SO₂ + 2H₂O
3)H₂⁺¹S⁺⁶O₄⁻²(р) + Fe⁰ = Fe⁺²S⁺⁶O₄⁻² + H₂⁰↑
Fe⁰ - 2ē -> Fe⁺² │2│1
2H⁺¹ + 2•1ē -> 2H⁰ │2│1
H₂SO₄(р) + Fe = FeSO₄ + H₂↑
4) Mg⁰ + H⁺¹N⁺⁵O₃⁻²(к) = Mg⁺²(N⁺⁵O₃⁻²)₂ + N₂⁺¹O⁻² + H₂⁺¹O⁻²
Mg⁰ - 2ē -> Mg⁺² │2│1│4
2N⁺⁵ + 2•4ē -> 2N⁺¹│8│4│1
4Mg + 10HNO₃(к) = 4Mg(NO₃)₂ + N₂O + 5H₂O
5) Ca⁰ + H⁺¹N⁺⁵O₃⁻²(р) = N⁻³H₄⁺¹N⁺⁵O₃⁻² + Ca⁺²(N⁺⁵O₃⁻²)₂ + H₂⁺¹O⁻²
Ca⁰ - 2ē -> Ca⁺² │2│1│4
N⁺⁵ + 8ē -> N⁻³ │8│4│1
4Ca + 10HNO₃(р) = NH₄NO₃ + 4Ca(NO₃)₂ + 3H₂O
Al + S2 = Al2S3
2Al + 2KOH + 6H2O = 2K[Al(OH)4] + 3H2
2Al + Fe2O3 = Al2O3 + 2Fe
2Al + 6HCl = 2AlCl3 + 3H2
2Al + 3CuSO4 = Al2(SO4)3 + 3Cu